Preventing recurrent cellulitis. (1st April 2019) - Teasdale, E.J.; Lalonde, A.; Muller, I.; Chalmers, J.; Smart, P.; Hooper, J.; El‐Gohary, M.; Thomas, K.S.; Santer, M.
Summary: Cellulitis is a painful skin infection that occurs most commonly in the lower leg. Around a third of people with cellulitis have repeat episodes, meaning they have it more than once. The only treatment shown to lower the risk of repeat episodes is long‐term antibiotics. Other possible ways to prevent repeat episodes include greater foot hygiene, applying cream to feet daily, exercise and wearing compression stockings. This study, from the U.K., aimed to find out people's views about cellulitis and different ways of preventing repeat episodes. Adults (aged 18 or over) who had had cellulitis were invited through doctors' surgeries, hospitals and local advertising to complete a survey, take part in an interview, or both. In total, 240 people completed a survey and 30 people took part in face‐to‐face interviews. The authors found that people in the study had wide‐ranging beliefs about what can cause cellulitis and were often unaware of the possibility of repeat episodes or how to prevent future episodes. Greater foot hygiene, applying cream to feet daily and exercise were more popular potential strategies for preventing repeat episodes than compression stockings or long‐term antibiotics. People had concerns about long‐term oral antibiotics for a variety of reasons, particularly those who had experienced only one episode of cellulitis. People were keen to find out about possible ways to prevent repeat episodes of cellulitis. More research is needed to find out how well the different ways actually prevent repeat episodes and what may fit best into people's daily lives.